Participación ciudadana en los espacios mediáticos televisivos de Riobamba durante el año 2022 - Silva Carrera, Juan José (2025)
The present research study stems from inquiries about the openness of television media in Riobamba to citizen participation. When individuals have the opportunity to identify their role within civil society, it grants them visibility and contributes to ensuring their opinions and demands are take into account. For this reason, the main objective of this study was to analyze the impact of citizen participation in television media spaces in Riobamba during 2022. The methodology employed was both qualitive and quantitative, using a content analysis matrix to review 72 news programs from local television media outlets: TVS Channel 13 and Ecuavisión Channel 29. The analysis included evaluation criteria related to the type of audience participation with the media, the topic of discussion, the number of participants, the communication channel, and an analysis of the 188 pieces of content reviewed during that year. Additionally, interviews were conducted with two experts in citizen participation who have significant experience in comparative matrices, which deepen the discussion on visibility, representativity, strategy, current challenges, effectiveness, and adaptation of citizen participation in television media. Among the results obtained, it was determined that local television media, within their agenda setting, do include reports or interview segments aimed at addressing citizens’ issues, particularly in the case of TVS Channel 13. Therefore, it was concluded that the lack of representativity in participation is not the responsibility of the media but rather the insufficient dissemination of participation mechanisms to citizens and the tools available for them to express their voice.